2011
DOI: 10.1017/s1479262111000451
|View full text |Cite
|
Sign up to set email alerts
|

Allelic variation at the EF-G locus among northern Moroccan six-rowed barleys

Abstract: A germplasm panel of 52 six-rowed barley landraces from northern Morocco was analysed by a Cleaved Amplified Polymorphic Sequences (CAPS) assay of a fragment of the elongation factor G (EF-G) gene. Forty-nine of these accessions carried allele A, and the other three carried allele D. The latter all originated from a narrow region close to the border with Algeria, whereas the former were represented across the whole collection area. Since six-rowed D allele carriers are present in North Africa, along with both … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 14 publications
0
4
0
Order By: Relevance
“…The evaluation of both SBCC parents revealed that they present a virulence pattern close to the resistance traditionally described as Rh4 (Graner and Tekauz 1996), later renamed by Bjørnstad et al (2002) as Rrs1 Rh4 , to indicate that it belongs to the Rrs1 locus. This resistance seems typical of accessions originating in North Africa or the Western Mediterranean region: CIho 3515 is Spanish, Osiris and Malebo (parent of Yerong) from Algeria and La Mesita is from Egypt, along one of the possible paths of expansion of barley from the Fertile Crescent towards the West (Baba et al, 2011;Igartua et al 2013). Therefore, it may have evolved in response to pathotypes prevalent in that region.…”
Section: Discussionmentioning
confidence: 96%
“…The evaluation of both SBCC parents revealed that they present a virulence pattern close to the resistance traditionally described as Rh4 (Graner and Tekauz 1996), later renamed by Bjørnstad et al (2002) as Rrs1 Rh4 , to indicate that it belongs to the Rrs1 locus. This resistance seems typical of accessions originating in North Africa or the Western Mediterranean region: CIho 3515 is Spanish, Osiris and Malebo (parent of Yerong) from Algeria and La Mesita is from Egypt, along one of the possible paths of expansion of barley from the Fertile Crescent towards the West (Baba et al, 2011;Igartua et al 2013). Therefore, it may have evolved in response to pathotypes prevalent in that region.…”
Section: Discussionmentioning
confidence: 96%
“…The most relevant information comes from the interpretation of results on nucleotide variation at the cMWG699 locus (which encodes elongation factor G), and is linked closely to VRS1, the main locus that determines spike type in barley. The D haplotype of this locus was described byTanno et al (2002) andBaba et al (2011) to be characteristic of the Western Mediterranean region, because it occurred only in some six-rowed and two-rowed barley accessions from North Africa and in Moroccan wild barley Tanno et al (2002). interpreted the distribution of haplotypes for this gene across germplasm groups as indirect evidence to support the multiple origin hypothesis for six-rowed barley.Baba et al…”
mentioning
confidence: 98%
“…Considering together the presence of the precursor allele of Vrs1.b5 (vrs1.a2) exclusively in Western Europe and, in lower frequencies, in Morocco (Casas et al 2005, Baba et al 2011, and data derived from Digel et al 2016, andRussell et al 2016), and the discovery of Vrs1.b5 in Spanish landraces, we hypothesize that this new allele is native to the western part of the Old World.…”
Section: Origin Of Vrs1b5mentioning
confidence: 91%
“…Several surveys done with this marker concluded that the D-type (associated to vrs1.a2 and Vrs1.b2) was found preferentially in the Mediterranean region (Tanno et al 1999(Tanno et al , 2002Casas et al 2005;Baba et al 2011), but it was also present in winter six-rowed cultivars from Germany, France, and other western European countries (Casas et al, 2005). Since both two-and six-rowed barleys carrying the D allele are present in North Africa, Baba et al (2011) proposed that the origin of the D allele was in Morocco. Our results illustrate that the D allele is profusely present in Spanish six-rowed landraces, most of them with the vrs1.a2 allele, and in a small group of two-rowed landraces featuring the new Vrs1.b5 allele.…”
Section: Origin Of Vrs1b5mentioning
confidence: 99%